RE-DESIGN APLIKASI KNOWLEDGE MANAGEMENT SYSTEM BERBASIS SITUS WEB PADA ASOSIASI DOSEN INTEGRATOR DESA DENGAN DESIGN THINKING - Nasution, Arman Hakim; Zunaidi, Rizqa Amelia; Putra, Perdana Suteja; Baskara, Dominggo Bayu (Abdimas Awang Long, 2024)
One of the administrative services commonly carried out by lecturer associations is the announcement of scientific collaboration activities between members. At the Association of Village Integrator Lecturers (ADIDES), until now, the process for submitting scientific collaboration activities between members is still done manually. This manual approach, although effective, requires more time because it involves manual confirmation and input by the website administrator for each announcement of scientific collaboration activities. Therefore, in the latest Community Service (PKM) activity, a website-based Knowledge Management System (KMS) application was designed, allowing each association member to add activities and collaborate independently. It is hoped that this website-based KMS application can become a means of communication and information dissemination between association members and the general public who are interested in the scientific collaboration programs offered by ADIDES. This website-based KMS ADIDES redesign uses a design thinking framework. The design thinking method includes five stages, namely empathize, define, generate ideas, create a prototype, and test. The use of a design thinking framework is expected to produce designs that are superior to previous sites. The results of the SUS (System Usability Scale) test on the KMS design based on the ADIDES website show that the design is well received by users and can be used more widely.